Priority directions for increasing technological efficiency in cotton-textile clusters of regions - Shukurov Ulugbek Shokirovich, (THE INNOVATION ECONOMY, 2026)
The article analyzes the importance of clusters and directions for improving technological efficiency in cotton-industrial clusters of the Kashkadarya region, and also examines the importance of introducing innovative technologies.